2013
DOI: 10.1016/j.jyp.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and its antioxidant activity of a newly isolated Streptomyces coelicoflavus BC 01 from mangrove soil

Abstract: The results of the present investigation proven that actinomycetes isolated from mangroves are potent source of antioxidants. The strain BC 01 exhibited a potential in vitro antioxidant activity; studies of actinomycetes from mangrove soil can be useful in discovery of novel species to get novel drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…AM-S1 isolated from forest humus soil in Gyeongsan, South Korea where ethyl acetate extract exhibited higher activity as compared to the lyophilised cell-free supernatant. According to Rao and Rao (2013) , the extracts of Actinobacteria isolated from mangrove soil of Vishakhapatnam region showed 46–70% DPPH scavenging activity and 68–78% FRAP activity at 20 μg/mL concentration. Karthik et al (2014) reported an extracellular protease produced by a marine Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AM-S1 isolated from forest humus soil in Gyeongsan, South Korea where ethyl acetate extract exhibited higher activity as compared to the lyophilised cell-free supernatant. According to Rao and Rao (2013) , the extracts of Actinobacteria isolated from mangrove soil of Vishakhapatnam region showed 46–70% DPPH scavenging activity and 68–78% FRAP activity at 20 μg/mL concentration. Karthik et al (2014) reported an extracellular protease produced by a marine Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was proven that the ocean floor possesses many unique forms of Actinobacteria ( Fenical and Jensen, 2006 ). Actinobacteria are widely distributed in intertidal zones, mangroves, seawaters, animals, plants, sponges, and in ocean sediments ( Goodfellow and Williams, 1983 ; Castillo et al, 2005 ; Jensen and Mafnas, 2006 ; Ramesh and Mathivanan, 2009 ; Sun et al, 2010 ; Xiao et al, 2011 ; Rao and Rao, 2013 ). Actinobacteria from the marine environment are considered as a promising source of pharmaceutically important compounds because of a different kind of unique adaptation characteristics ( Fenical and Jensen, 2006 ; Jose and Jha, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alternative antioxidants from natural sources are more preferable and many recent studies have shown that besides plants as rich source of antioxidants (Wong et al, 2012 ; Tan et al, 2015 ), microorganisms can be used for the production of natural antioxidants. Recently, many studies reported that mangrove Streptomyces produced antioxidative agents (Rao and Rao, 2013 ; Ser et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…Extract from Streptomyces sp. SRDP‐H03 and Streptomyces coelicoflavus BC 01 isolated from soil also scavenged the DPPH. The IC 50 value of protocatechualdehyde produced from Streptomyces lincolnenis M‐20 was 0.2 mmol L −1 and ED 50 value of surugapyrone A produced from Streptomyces coelicoflavus strain USF‐6280 was 4.2 mmol L −1 [54].…”
Section: Resultsmentioning
confidence: 97%